Regulatory T Cells Restrain Pathogenic T Helper Cells during Skin Inflammation - Hartwig, Tom; Zwicky, Pascale; Schreiner, Bettina; Yawalkar, Nikhil; Cheng, Phil; Navarini, Alexander; Dummer, Reinhard; Flatz, Lukas; Conrad, Curdin; Schlapbach, Christoph; Becher, Burkhard (Cell reports (Cambridge), 2018)
Psoriasis is a chronic relapsing, remitting interleukin (IL)-23/IL-17-driven skin disease mediated by the interplay of T cells and polymorphonuclear granulocytes. Although preclinical studies have provided insights into the mechanisms of disease initiation, the underpinnings of natural disease remission remain largely unknown. Here, we addressed the contribution of regulatory Foxp3+ T cells (Treg cells) in psoriasiform skin inflammation and remission using the Aldara-skin inflammation model in combination with the inducible depletion of Foxp3+ Treg cells. Loss of Treg cells exacerbated skin inflammation, but this did not involve increased γδ T cell expansion or the local production of the psoriasis-associated cytokines IL-17A, IL-17F, and IL-22, which are the main driving forces of disease development. Instead, Treg cells suppressed the infiltration of granulocyte-macrophage colony-stimulating factor (GM-CSF)-producing CD4+ T cells into the lesioned skin, and neutralizing GM-CSF in Treg cell-deficient mice reversed hyper-inflammation, resulting in disease regression. Therefore, we identified a non-redundant role of Treg cells restraining skin inflammation and mediating skin homeostasis. [Display omitted] •Treg cells infiltrate into psoriasiform skin lesions•Treg cells limit the exacerbation of skin inflammation and initiate disease remission•GM-CSF+CD4+ T cells emerge in Treg-cell-depleted skin•Neutralization of GM-CSF reverses exacerbated skin inflammation to wild-type levels The contribution of Treg cells to psoriasis is poorly understood. By combining inducible depletion of Treg cells with the Aldara model of psoriasiform inflammation, Hartwig et al. reveal a non-redundant role of Treg cells in promoting the remission of skin inflammation by limiting invasion of CD4+ GM-CSF-producing T cells into psoriatic skin.